The duty of fair representation – effective protection for individual rights in collective agreements? - Adell, B. (Relations industrielles / Industrial Relations, 1970)
The author uses the example of Fisher against Pemberton to illustrate the case of an individual employee action against his union for breach of the union*s duty of fair representation.